Assessment of Innovation Intensity: the Case of USA - Lavrovsky, Boris Leonidovich (Economy of Regions, 2018)
In the literature, some categories and terms related to technological progress and innovation activity are often considered as synonyms or differences between them are not completely clear. Therefore, the author attempts to distinguish these terms and to link them as well. The measurement and assessment of the innovation intensity is based on the ratio of investment efforts and consequent indicators productivity trends. The better this ratio is, the higher the innovation activity is. I propose two methods based on this approach. The first method supposes the measurement of the innovation intensity via the decomposition of the productivity gain into the factors that generate it. These factors are the dynamics of capital productivity and the capital-labour ratio (in logarithms). Thus, the assessment of the innovation intensity is a part of the productivity gain, which is due to the capital productivity dynamics. The second method is based on the special parameter, which characterizes the investment potential of growth. This potential is the need for investments to increase in productivity of single intensity. Calculations based on US statistics since the early 1960s illustrate the role of the innovation factor in certain quantitative assessments. In general, for the period 1961-2014, about 3/4 of the productivity gain is due to the capital-labour ratio growth, and only % results from the capital productivity growth. In 1981-2000, about a half of the productivity gain was due to the innovation factor. This innovation factor is investments in breakthrough technologies. Furthermore, I found out that for a very long period, the investment rate alone had very little effect on the significant changes in the growth productivity rates. At the same time, from the beginning of the 1980s, a reduction in the relative demand for investment with almost the same investment allowed to stop the threatening tendency of reducing the productivity growth rates. The obtained results can be useful for the development of the Russian investment strategy, because the intensification of innovation activity is a basic condition for expanding investment activity.